2021
DOI: 10.1007/s13204-021-01738-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nano- and micro-sized additives on 3D printable cementitious and alkali-activated composites: a review

Abstract: Additive manufacturing (AM), also referred as 3D printing, is a technology that enables building automated three-dimensional objects in a layer-by-layer manner. AM of cement-based and alkali-activated composites has gathered attention over the last decade and is one of the most rapidly developing civil engineering fields. Development of proper mixture compositions which are suitable in fresh and hardened state is one of the key challenges of AM technology in construction. As the behaviour of cement-based mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 107 publications
1
13
0
Order By: Relevance
“…In the construction sector, particularly in concrete industry, crystalline SiO 2 is widely applied in the shape of aggregates and smaller sized fillers. As amorphous SiO 2 it is used to accelerate cement hydration [10,11] and tailor 3D printing properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the construction sector, particularly in concrete industry, crystalline SiO 2 is widely applied in the shape of aggregates and smaller sized fillers. As amorphous SiO 2 it is used to accelerate cement hydration [10,11] and tailor 3D printing properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…The silica, as an additive, is used in coatings, food, and biomedical applications. For example, silica as a bio-safe additive can be incorporated along with silver nanoparticles to improve the antibacterial properties and corrosion properties of biomaterials [13][14][15][16][17][18][19][20][21][22][23]. The amorphous silica nanoparticles extracted from natural sources, such as rice husk and fly ash, can be used as a nucleating agent when added to thermoplastic polymers in very low amounts, owing to their large surface area [24].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have used nanomaterials to modify the fresh behavior of concrete in favor of 3D concrete printing [ 166 , 167 ]. Chougan et al reported an increase in yield stress, shape retention, and buildability of alkali-activated cementitious materials with the addition of nano-attapulgite clay particles.…”
Section: Printable MIX Designs and Influence Of Concrete Ingredients On Rheologymentioning
confidence: 99%